THE ROLE OF STRUCTURAL CHANGES IN THE DIGITALIZATION OF THE INVESTMENT ECONOMY - Turayev Bakhodir Tokhirovich (Scholar Express Journals, 2023)
This article highlights the role of structural changes in the conditions of digitalization of the investment economy. Also, the available literature and legal documents on ways of attracting foreign investments to the economy of Uzbekistan and their effective use were analyzed. In addition, it is scientifically based that the development of investment activities in accordance with the conditions of the economic environment, ensuring their activity in all aspects of the economic life of the society, modernization of the national production process and ensuring stable economic growth.
Keywords: investment economy; digitization conditions; foreign investments